Commissioning of a clinical pencil beam scanning proton therapy unit for ultra‐high dose rates (FLASH). Issue 7 (25th May 2021) - Nesteruk, Konrad P.; Togno, Michele; Grossmann, Martin; Lomax, Anthony J.; Weber, Damien C.; Schippers, Jacobus M.; Safai, Sairos; Meer, David; Psoroulas, Serena
Abstract : Purpose: The purpose of this work was to provide a flexible platform for FLASH research with protons by adapting a former clinical pencil beam scanning gantry to irradiations with ultra‐high dose rates. Methods: PSI Gantry 1 treated patients until December 2018. We optimized the beamline parameters to transport the 250 MeV beam extracted from the PSI COMET accelerator to the treatment room, maximizing the transmission of beam intensity to the sample. We characterized a dose monitor on the gantry to ensure good control of the dose, delivered in spot‐scanning mode. We characterized the beam for different dose rates and field sizes for transmission irradiations. We explored scanning possibilities in order to enable conformal irradiations or transmission irradiations of large targets (with transverse scanning). Results: We achieved a transmission of 86% from the cyclotron to the treatment room. We reached a peak dose rate of 9000 Gy/s at 3 mm water equivalent depth, along the central axis of a single pencil beam. Field sizes of up to 5 × 5 mm 2 were achieved for single‐spot FLASH irradiations. Fast transverse scanning allowed to cover a field of 16 × 1.2 cm 2 . With the use of a nozzle‐mounted range shifter, we are able to span depths in water ranging from 19.6 to 37.9 cm. Various dose levels were delivered with precision within less than 1%. Conclusions: We have realized a proton FLASH irradiation setup able to investigate continuously a wide dose rate spectrum, from 1 to 9000 Gy/s in single‐spot irradiation as well as in the pencil beam scanning mode. As such, we have developed a versatile test bench for FLASH research.